Weapons of mass instruction: a schoolteacher's journey through the dark world of compulsory schooling - Kaptan, Orhun (SPRINGER, 2022)
This study is a book review of John Taylor Gatto's work titled Weapons of Mass Instruction: A Schoolteacher's Journey through the Dark World of Compulsory Schooling. The purpose of this study is to evaluate strengths and weaknesses of the book, while providing an insight about how the book was organized and what the main theme is. Although the book was published in 2010, its translations to other languages were carried out later; as an illustration, it was published in Turkey in 2018. Hence, this book review may also provide a new perspective which would make a longitudinal comparison possible. The strongest aspect of the book reviewed can be nominated as its success in establishing a concrete view of the current education system in the USA from a chronological perspective, which reproduces a gigantic social stratum of consumerist, self-alienated and harmless voters. The foremost weakness of the book is the author's proposition of a new approach entitled by the author as open-source learning, which relies on an irrational sampling and could pave the way for child labor, where child abuse is a major problem. All in all, the language used in the book makes it possible for every individual from and out of educational spheres to evaluate education system from a critical perspective.
Keywords: Education & Educational Research